2016
DOI: 10.1016/j.neuroimage.2016.02.004
|View full text |Cite
|
Sign up to set email alerts
|

In vivo quantification of demyelination and recovery using compartment-specific diffusion MRI metrics validated by electron microscopy

Abstract: There is a need for accurate quantitative non-invasive biomarkers to monitor myelin pathology in vivo and distinguish myelin changes from other pathological features including inflammation and axonal loss. Conventional MRI metrics such as T2, magnetization transfer ratio and radial diffusivity have proven sensitivity but not specificity. In highly coherent white matter bundles, compartment-specific white matter tract integrity (WMTI) metrics can be directly derived from the diffusion and kurtosis tensors: axon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
162
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 163 publications
(175 citation statements)
references
References 55 publications
13
162
0
Order By: Relevance
“…In contrast, NDI always drops dramatically within lesions, similar to myelin density MSF. This finding is not surprising as NDI is a surrogate index equivalent to NSF/(1–MSF)26, 43 (post hoc analysis confirms a correlation between these two measures). Although altered exchange of water between intra/extra‐axonal space (i.e., permeability)40, 44 may have contributed to the observed patterns of NDI, it is expected that variations of myelin density would also contribute.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…In contrast, NDI always drops dramatically within lesions, similar to myelin density MSF. This finding is not surprising as NDI is a surrogate index equivalent to NSF/(1–MSF)26, 43 (post hoc analysis confirms a correlation between these two measures). Although altered exchange of water between intra/extra‐axonal space (i.e., permeability)40, 44 may have contributed to the observed patterns of NDI, it is expected that variations of myelin density would also contribute.…”
Section: Discussionmentioning
confidence: 55%
“…Future validation of our preliminary findings could include: analysis of tissue from areas beyond the spinal cord; extension of the histology to the third dimension50, 51; further confirmation from in vivo data; characterization of more complex morphological features of glial cells52; more accurate diffusion MRI signal modeling43, 53; analysis of other quantitative MRI metrics (such as those from relaxometry, magnetization transfer techniques or susceptibility imaging).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Validation studies comparing WMTI indices to histology and electron microscopy [23][24][25][26] have largely confirmed the ability of WMTI to detect microstructural changes in WM. While other frameworks for DKI-based estimation of tissue model parameters have been proposed [27,28], a recent comparative study showed WMTI to be the most widely applicable [27].…”
Section: Introductionmentioning
confidence: 89%
“…More complex biophysical models along with sophisticated measurements can more precisely explain the measured signal 119 and aid interpretation by providing specific markers of microstructure changes [120][121][122] . For example, the diffusion signal measured at a range of q values (gradient areas) exhibits a characteristic diffraction pattern in which zero crossings indicate the size of restricted compartments 123 .…”
Section: The Futurementioning
confidence: 99%